Chaos Theory in Organisations: A Real Time Management Approach for Improvisation - Awele V. OHAEGBU; Chinonye L. MOSES (Communications of International Proceedings, 2021)
This study examines how real time management can be effectively used for improvisation in organizations. Conceptual, theoretical and empirical studies were reviewed to establish time approaches on a continuum to derive real time. Chaos theory was used to describe nonlinear dynamic organisational system which creates turbulent work environment. It was revealed that there are underlying factors for organisations to adopt asides planning to cater for disturbances and distortions as they occur. These factors include merging time perspectives, experimental workplace culture, employee’s skills and expertise, communication and information. It was recommended that organisations should not accept time only as a social concept only for deadlines but as a tool for improvisation which provides a realistic basis and panacea for handling unplanned occurrences.
Keywords: Dynamic; Improvisation; Planning; Time management